Hubungan Faktor-Faktor yang Mempengaruhi Motivasi Ibu dalam Pelaksanaan Senam Hamil di Wilayah Kerja Puskesmas Kuta Baro Kabupaten Aceh Besar - Nurul Sakdah; Fauziah Fauziah; Urip Pratama; Syukriadi Syukriadi; Amrina Rasyada (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Pregnancy exercises are beneficial for both mother and fetus. In mothers to reduce pain during childbirth and can strengthen the pelvic floor muscles and the mother's abdominal wall, improve blood circulation so as to accelerate the process of childbirth. This study aims to determine the relationship of factors that influence the motivation of mothers in the implementation of pregnant gymnastics in the Kuta Baro Community Health Center Working Area, Aceh Besar Regency. This study uses an analytic design that uses a cross sectional approach. The research population of all pregnant women in the Kuta Baro puskemas working area was 730 people, the research sample of pregnant women was 88 respondents. The sampling technique used in this research was Accidental Sampling. This research instrument uses a questionnaire sheet. The data collection was conducted on March 25 to April 19, 2023 in the Kuta Baro Community Health Center work area. The results showed that there was a significant relationship between the knowledge factor and the implementation of pregnant gymnastics value (p=0.000). There is a significant relationship between the attitude factor and the implementation of pregnant gymnastics value (p=0.000). There is significant relationship between the factor of husband's support with implementation of pregnant gymnastics value (p=0.019). Conclusion There is a relationship between the factors that influence mothers in the implementation of pregnant gymnastics in the Kuta Baro Community Health Center Working Area, Kuta Baro District, Aceh Besar. It is expected that respondents can maximize the factors that exist in following regular pregnancy exercises.